Effectiveness of Interventional Strategies in Modulating Knowledge and Attitude of Health Care Professionals for Promoting Organ Donation: A Study in Tertiary Care Public Hospital of North India. Issue 3 (July 2020) - Mahajan, Pranay; Koushal, V.; Chhabra, R.; Dhaliwal, N.; Pandey, N.; Kaur, R.
Objective: To evaluate the impact of interventional "educational module" on knowledge and attitude regarding organ donation amongst resident doctors and nurses in the Institute of National Importance. Study Design: Interventional and prospective. Methods: We devised an interactive educational module covering various aspects of organ donation through a series of audiovisual lectures and information booklets. Resident doctors and nurses posted in those areas of the 1948-bedded Postgraduate Institute of Medical Education and Research (PGIMER), where head injury patients were treated and were subject to intervention using this module. The pre and postinterventional scores of their knowledge and attitude regarding organ donation were compared to find out impact of the intervention. Results: A total of 242 nurses and 87 resident doctors participated in this research. Higher knowledge score was observed preintervention amongst doctors as compared to nurses. Significant improvement was seen in total knowledge scores of both groups postintervention. Doctors had better scores for the "concept of organ donation, " while nurses were more familiar with "procedures and protocols." Both had low knowledge about "clinical criteria for brain death" and "legal issues" preintervention which improved significantly postintervention. The positive impact of intervention was also observed on attitude in both categories. A significant impact of intervention was observed on overall propensity of doctors and nurses to promote organ donation, for pledging their own organs and for counseling of the patient/attendants on this cause. Conclusion: Scientifically designed educational modules have a promising role in improving awareness and attitude of health care professionals regarding organ donation and their propensity to be prospective donors, effective counselors, and advocates of organ donation.